Techno-economic assessment of thin lithium metal anodes for solid-state batteries - Burton, M; Narayanan, S; Jagger, B; Olbrich, LF; Dhir, S; Shibata, M; Lain, MJ; Astbury, R; Butcher, N; Copley, M; Kotaka, T; Aihara, Y; et al. (Nature Research, 2024)
Solid-state lithium metal batteries show substantial promise for overcoming theoretical limitations of Li-ion batteries to enable gravimetric and volumetric energy densities upwards of 500 Wh kg−1 and 1,000 Wh l−1, respectively. While zero-lithium-excess configurations are particularly attractive, inhomogeneous lithium plating on charge results in active lithium loss and a subsequent coulombic efficiency penalty. Excess lithium is therefore currently needed; however, this negatively impacts energy density and thus limiting its thickness is essential. Here we discuss the viability of various technologies for realizing thin lithium films that can be scaled up to the volumes required for gigafactory production. We identify thermal evaporation as a potentially cost-effective route to address these challenges and provide a techno-economic assessment of the projected costs associated with the fabrication of thin, dense lithium metal foils using this process. Finally, we estimate solid-state pack costs made using thermally evaporated lithium foils.